2015
DOI: 10.1371/journal.pone.0135573
|View full text |Cite
|
Sign up to set email alerts
|

The Fecal Virome of Children with Hand, Foot, and Mouth Disease that Tested PCR Negative for Pathogenic Enteroviruses

Abstract: Hand, foot, and mouth disease (HFMD) affects infant and young children. A viral metagenomic approach was used to identify the eukaryotic viruses in fecal samples from 29 Thai children with clinical diagnosis of HFMD collected during the 2012 outbreak. These children had previously tested negative by PCR for enterovirus 71 and coxsackievirus A16 and A6. Deep sequencing revealed nine virus families: Picornaviridae, Astroviridae, Parvoviridae, Caliciviridae, Paramyxoviridae, Adenoviridae, Reoviridae, Picobirnavir… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
8
0

Year Published

2016
2016
2021
2021

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 19 publications
(9 citation statements)
references
References 105 publications
0
8
0
Order By: Relevance
“…The clinical phenotype resulting from viral infections is determined by complex interactions of multiple factors [ 49 ]. Besides the virus, host factors, the intestinal virome, coinfection with more than two EV types, and the environment can also influence HFMD outcome [ 6 , 50 55 ]. No coinfection was found in patients with severe HFMD based on the traditional experimental methods used in this study.…”
Section: Discussionmentioning
confidence: 99%
“…The clinical phenotype resulting from viral infections is determined by complex interactions of multiple factors [ 49 ]. Besides the virus, host factors, the intestinal virome, coinfection with more than two EV types, and the environment can also influence HFMD outcome [ 6 , 50 55 ]. No coinfection was found in patients with severe HFMD based on the traditional experimental methods used in this study.…”
Section: Discussionmentioning
confidence: 99%
“…Exploring the use of next-generation sequencing based assay as a diagnostic tool was an objective in many recent reports [ 30 – 32 ]. In addition, next-generation sequencing has been shown to be able to establish the diagnostics in swabs from HFMD patients that were enterovirus specific PCR negative [ 33 ]. Similarly, our assay could sequence and provide correct serotype information of the targeted enteroviruses in all tested samples with Cp values between 20.9 and 33.2, although we did not test our assay on samples with lower viral load (i.e.…”
Section: Discussionmentioning
confidence: 99%
“…Such a case has been made for the marine vesiviruses in studies that have reported a higher prevalence of vesivirus antibodies in certain patient groups with hepatic disease ( 36 , 37 ). It is noteworthy that virus discovery efforts by deep sequencing have not detected vesivirus RNA in human clinical samples ( 49 ), but vesivirus sequences have been detected with these techniques in sea lions and other wild animals ( 50 ). These data suggest that species tropism, largely determined by receptor specificity, is responsible for the host range of these viruses and that interspecies transmission is a rare event.…”
Section: Discussionmentioning
confidence: 99%